Fundamentals of digital logic with verilog design - Brown, Stephen D.; Vranesic, Zvonko G. (McGraw-Hill, 2014)
Fundamentals of Digital Logic With Verilog Design is intended for an introductory course in digital logic design. The main goals are (1) to teach students the fundamental concepts in classical manual digital design, and (2) illlustrate clearly the way in which digital circuits are designed today, using CAD tools. Use of CAD software is well integrated into the book. Some excellent CAD tools are available free of charge. For example, the Altera Corporation has its Quartus II CAD software, used for implementing designs in programmable logic devices such as FPGAs.